Gravitational lensing by galaxy clusters - Sigurdarson, Haukur (My University, 2010)
Massive galaxy clusters can be utilized as giant natural telescopes; they magnify background galaxies giving us a view into the population of low flux density galaxies at high redshifts. Observations of such lensed galaxies require knowledge of the mass distribution of the lens in order to estimate the magnification of detected sources. In this work we present a computer program that simulates galaxy clusters as a superposition of spherically symmetric components represented by Navarro, Frenk & White (NFW) mass profiles and generates magnification maps. Those maps can be used to interpret observations of the (magnified) flux density of sources in cluster fields and to estimate the intrinsic flux density of the sources. We also discuss a way to correct for the effects of gravitational lensing in the analysis of number counts of submm galaxies that lie behind gravitational lenses.
Keywords: Astronomi, astrofysik och kosmologi; Astronomy, Astrophysics and Cosmology